2010
DOI: 10.3109/09638281003763796
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and cross-cultural validation of the Turkish version of Manual Ability Classification System (MACS) for children with cerebral palsy

Abstract: The Turkish version of the MACS is found to be valid and reliable, and is suggested to be appropriate for the assessment of manual ability within the Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 21 publications
3
44
0
5
Order By: Relevance
“…We found that the Korean version of the MACS demonstrated high reliability coefficients, similar to those observed for other versions of the MACS (Eliasson et al 2006(Eliasson et al , 2007Akpinar et al 2010). These high reliabilities were likely due to the careful translation.…”
Section: Discussionsupporting
confidence: 82%
“…We found that the Korean version of the MACS demonstrated high reliability coefficients, similar to those observed for other versions of the MACS (Eliasson et al 2006(Eliasson et al , 2007Akpinar et al 2010). These high reliabilities were likely due to the careful translation.…”
Section: Discussionsupporting
confidence: 82%
“…We used the Turkish MACS in this study14 ) . Cultural validation of MACS was published by Akpinar P et al 15. ) ; 3) CFCS was used to classify the everyday communication performance of children with CP7 ) .…”
Section: Methodsmentioning
confidence: 99%
“…In several studies, the inter-and intrarater reliability of the MACS has been found to be good to excellent between therapists as well as between parents and therapists, varying from 0.73 to 0.98 and 0.91 to 0.98 respectively. 2,[4][5][6][7][8][9][10][11] There is also evidence supporting the stability of MACS classifications over a short period. In a previous study, the intraclass correlation coefficient (ICC) was high (0.92) and 67% of the children remained at the same level over a period of 1 year when scored by caregivers.…”
mentioning
confidence: 94%